1980
DOI: 10.1177/002224378001700105
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis of Buyer Behavior under Conditions of Crowding

Abstract: By use of path analysis on data from 600 shoppers, the authors explore the sequential relationships among several variables pertinent to retail crowding. Results furnish evidence that perceived crowding systematically affects shopping behavior and consumers’ feelings about retail outlets and shopping trips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 8 publications
2
79
0
8
Order By: Relevance
“…We constructed the questions by adopting items from previous work that delineates social separateness (Vignoles, Chryssochoou, and Breakwell 2002) and modifying them for our context. Finally, the violation of personal space was measured with three items on a Likert-type scale (e.g., "I would feel my personal space is violated"; a ¼ .94), adopted from Harrell, Hutt, and Anderson (1980). The construct correlation matrix is presented in web appendix W3.…”
Section: Methodsmentioning
confidence: 99%
“…We constructed the questions by adopting items from previous work that delineates social separateness (Vignoles, Chryssochoou, and Breakwell 2002) and modifying them for our context. Finally, the violation of personal space was measured with three items on a Likert-type scale (e.g., "I would feel my personal space is violated"; a ¼ .94), adopted from Harrell, Hutt, and Anderson (1980). The construct correlation matrix is presented in web appendix W3.…”
Section: Methodsmentioning
confidence: 99%
“…Negative feelings caused by in-store crowding have been found to translate into lower patronage for retail stores (e.g., Machleit 1990, Eroglu et al 2005). Another study found that in overcrowded stores potential buyers may even deviate from their planned shopping experience by spending less money than planned or even leaving without making a purchase (Harrell et al 1980). Finally, crowding in retail environments could also affect the performance of the sales associates who interact with the dissatisfied and/or aggressive customers (Lepore 1994), having implications for the overall store performance.…”
Section: Hypothesesmentioning
confidence: 99%
“…Bu adaptasyon stratejilerini şehirde/destinasyonda daha az zaman harcama, amaçlanan davranışları/planları yerine getirmeme, keşfetme davranışında bulunmamayı içermektedir (Milgram, 1970(Milgram, : 1461(Milgram, -1462. Perakende kapsamında bu stratejiler mağazada daha az zaman harcama, alışverişi tamamlamama, daha az ürün satın alma/ürün satın almama gibi davranışlar olarak tanımlanmıştır (Harrell, Hutt ve Anderson, 1980;Hui ve Bateson, 1991;Machleit, Kellaris ve Eroğlu, 1994;Eroğlu, Machleit ve Barr, 2005;Machleit Eroğlu ve Mantel, 2000). Pazarlama ve turizm bağlamında bir hizmet uzantısı olarak ele alınan kalabalığın bireylerin duyguları ve davranışları üzerinde etkili olduğu belirlenmiştir (Harrell, Hutt ve Anderson, 1980;Hui ve Bateson, 1991;Turley ve Millman, 2000;Machleit Eroğlu ve Mantel, 2000;Wakefield, Blodgett ve Sloan 2000;Tse, Sin ve Yim, 2002;Lee ve Graefe, 2003Eroğlu, Machleit ve Barr, 2005Newmann, 2007;Edwards ve Gustafsoon, 2008).…”
Section: Destinasyon Uzantıları öLçeğiunclassified